Reliability enhancement of electrical power system including impacts of renewable energy sources: a comprehensive review. Issue 10 (3rd April 2020) - Kumar, Sachin; Saket, R.K.; Dheer, Dharmendra Kumar; Holm‐Nielsen, Jens Bo; Sanjeevikumar, P.
Abstract : This study presents a comprehensive survey on the reliability evaluation of the electrical network system. The impacts of integration of new and renewable energy sources (electric vehicle, energy storage system, solar, and wind) on the reliability of electrical power system (EPS) are discussed. The impacts of these renewable sources have merits/demerits when these sources are integrated with the conventional electric power system. However, the merits are predominant as it includes unlimited, free, and cost‐effective resources. The recent researches depict that the uncertainties of renewable energy resources leads to the probabilistic and reliability analyses of EPS. EPS includes offshore and onshore wind farms, micro‐grid, energy storage system, and other high voltage grids. It also contains the failure‐prone components related to the power systems. For the accomplishment of these aspects, the handling methods of uncertainty parameters in generation, transmission, and distribution systems are discussed. The incorporation of electric vehicles, wind energy system, and energy storage system for reliability assessment is also discussed briefly. This study also presents the scope of a new research area for the researchers on the reliability assessment of renewable energy integrated power system.